1976
DOI: 10.1136/hrt.38.7.665
|View full text |Cite
|
Sign up to set email alerts
|

Congenital aortic valve disease with rupture of mitral chordae tendineae.

Abstract: A new clinical entity is described in which free aortic regurgitation from congenital aortic valve disease caused rupture of the chordae to the anterior leaflet of the mitral valve in 7 men aged 45 to 63years (mean 52 years); 2 of the patients also had rupture of chordae to the posterior leaflet. Comparing these patients with those with ruptured mitral chordae in association with rheumatic heart disease and patients with spontaneous chordal rupture, differences were evident. No patient had a history of rheumat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…A paucity of information is available concerning the morphogenesis and normal structure of the chordae tendineae and papillary muscles, the supportive elements of the left atrioventricular valve. This fact becomes highly significant with the knowledge that pathology of the chordae tendineae is a common finding in mitral valve disease (Morris et al, 1964;Ellis et al, 1966;Caulfield et al, 1971;Danilowicz et al, 1971;Manhas et al, 1971;Joseph et al, 1976;Rittenhouse et al, 1978;Frater et al, 1983).…”
mentioning
confidence: 99%
“…A paucity of information is available concerning the morphogenesis and normal structure of the chordae tendineae and papillary muscles, the supportive elements of the left atrioventricular valve. This fact becomes highly significant with the knowledge that pathology of the chordae tendineae is a common finding in mitral valve disease (Morris et al, 1964;Ellis et al, 1966;Caulfield et al, 1971;Danilowicz et al, 1971;Manhas et al, 1971;Joseph et al, 1976;Rittenhouse et al, 1978;Frater et al, 1983).…”
mentioning
confidence: 99%
“…6 The anatomy of the normal mitral valve has been meticulously studied. '6 31 Variation in the chordal arrangement and atypical chordae were encountered in 37 of the 50 hearts examined. In a more recent study" abnormalities were noted in the deposition of chordae tendineae in 36 32 Regarding complications and associated conditions in our series, 20 of the 50 patients suffered rupture of the chordae tendineae close to a point where secondary fibrous thickening and myxomatous tissue were prominent.…”
Section: Discussionmentioning
confidence: 93%
“…A 5 per cent incidence of atrial septal defect has been reported. 8 Returning once more to the valvar theory, histologically, myxomatous degeneration has consistently been documented.3338 With the exception of three contributions,'4 37 38 the normal histological structure has either not been mentioned or not taken into account and has led to the suggestion that the process of degeneration of the fibrosa is present.39…”
Section: Discussionmentioning
confidence: 99%
“…Another 1 cm of harvested inferior caval vein was smashed and the supernatant of homogenate for thrombolysis observation was collected in plasma plate, activity and content of tPA. All supernatant from the gene therapy group veins apparently had a thrombolysis zone in plasma plate and none had that appearance from another two control groups (Figure 2d) 2 , respectively. The contents of tPA in the gene therapy group were higher than those in the control group and the blank control group (Po0.01; Table 2).…”
mentioning
confidence: 96%
“…Valve replacement is an efficient method of treating valve dysfunction of heart valve diseases. [1][2][3] However, those patients who have had valve replacement operations with mechanical valves should take anticoagulation medicine for the rest of their lives where serious complications of thrombosis and over anticoagulation bleeding have been observed. [4][5][6] Tissue-type plasminogen activator (tPA) has a special and thorough thrombolysis on the thrombus in dynamic blood circulation.…”
mentioning
confidence: 99%